One-dimensional nanoreactor as well as preparation method and application thereof
By regulating the proportion of raw materials such as metal sources, carbon and nitrogen sources and sintering conditions in the preparation of one-dimensional nanoreactors, the high cost and low efficiency problems caused by traditional pyrolysis are solved, and the low-cost and efficient large-scale production of one-dimensional nanoreactors is achieved, and the stability and application potential of materials are improved.
Patent Information
- Application Number
- CN202411441733.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing one-dimensional nanoreactor production methods have problems of high cost and low efficiency, especially the traditional pyrolysis method has made it difficult to control the size of metal particles and the uneven morphology of carbon tubes, which limits its large-scale application.
A mixed liquid slurry with a specific molar ratio was prepared by mixing a metal source, a carbon-nitrogen source, a supplementary carbon source, an alkaline metal salt and a heteroatom source in a dispersant, and a one-dimensional nanoreactor was prepared after drying and sintering. This method controls the ratio of raw materials and sintering conditions, controls the size of metal particles and the morphology of carbon tubes, and achieves low-cost and efficient large-scale production.
It improves the final product output of the one-dimensional nanoreactor, reduces the mass loss of pyrolysis, reduces production costs, and ensures the morphology and structural stability of the material. It is suitable for applications in energy storage, catalysis and other fields.
Smart Images

Figure CN119549174A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of new chemical energy materials, and in particular to a one-dimensional nanoreactor and a preparation method and application thereof. Background Art
[0002] One-dimensional nanoreactors are nanocatalyst particles encapsulated in carbon tubes, which can be carbon nanospheres, carbon nanoprisms, long-range carbon nanotubes, etc. Carbon tubes can exchange electrons with encapsulated nanocatalysts to enhance the intrinsic catalytic performance of nanocatalysts. At the same time, the nanoscale reaction chamber allows reactants and catalysts to react for a long time without being affected by the external environment, thereby enhancing the reaction efficiency. The long-range one-dimensional electron and reactant transport path is conducive to ensuring the continuity of the reaction. Therefore, the one-dimensional nanoreactor is a new type of composite material with brand-new properties that achieves one plus one greater than two by integrating multiple components at the nanoscale.
[0003] One-dimensional nanoreactors occupy an important position in the development of nanomaterials and nanotechnology. Their unique structure and properties make them show great application potential in various application fields. One-dimensional nanoreactors are often used in the field of catalysis (electrocatalysis and photocatalysis), including electrocatalytic reactions such as oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER), as well as in the field of photocatalytic decomposition of water to produce hydrogen. Energy storage field: In energy storage devices such as lithium-ion batteries and supercapacitors, one-dimensional nanoreactors are widely used due to their excellent conductivity and high surface area. Sensor field: Due to their sensitive surface properties and directional transmission capabilities, one-dimensional nanoreactors are also often used to develop highly sensitive sensors.
[0004] At present, the main production methods of one-dimensional nanoreactors include electrospinning, template method, sol-gel method, pyrolysis method, hydrothermal method, chemical vapor deposition method (CVD method), etc. At present, except for the CVD method, the other methods have achieved laboratory-level preparation, which is far from the efficient preparation of large quantities. In particular, the production cost limits its application. For example, the pyrolysis method, the mass loss of raw materials in the pyrolysis of the traditional pyrolysis method is 80%-90%, and the final product output after subsequent processing is less than 5%, which greatly increases the production cost of the one-dimensional nanoreactor, resulting in its only small-scale application; in addition, the size of metal particles in the traditional pyrolysis method is not easy to control, and the morphology of carbon tubes is uneven, which makes it unable to effectively exert the excellent performance of the one-dimensional nanoreactor. Summary of the invention
[0005] Based on this, the purpose of the present invention is to provide a one-dimensional nanoreactor and a preparation method thereof, to control the reaction process and the ratio of reaction raw materials, to increase the final product yield, to control the metal particle size and carbon tube morphology, so as to realize low-cost and efficient large-scale production of one-dimensional nanoreactor.
[0006] Part I:
[0007] The method for preparing a one-dimensional nanoreactor according to the present invention comprises the following steps:
[0008] Mixing a metal source, a carbon and nitrogen source, a supplemental carbon source, an alkaline metal salt, and a heteroatom source in a dispersant to obtain a mixed liquid slurry;
[0009] Drying the mixed liquid slurry to obtain a precursor;
[0010] Sintering the precursor to obtain a one-dimensional nanoreactor;
[0011] The molar ratio of the metal source, carbon and nitrogen source, supplementary carbon source, alkaline metal salt, and heteroatom source is (0.1-99): (5-30): (0-15): (0-10): (0-20);
[0012] The metal source includes at least one of nitrates, chlorides, sulfates, phosphates, oxides, and hydroxides of iron, manganese, nickel, cobalt, copper, zinc, or aluminum;
[0013] The carbon and nitrogen source includes at least one of urea, pyridine, polyaniline, cyanamide, dicyandiamide, melamine and dopamine.
[0014] The supplementary carbon source comprises at least one of citric acid, glucose, sucrose, starch, maltose, chitosan, polyvinyl pyrrolidone, polyethylene, polypropylene, polyethylene glycol, polyvinyl alcohol, and polystyrene;
[0015] The alkaline metal salt includes at least one of nitrates, chlorides, sulfates, sulfates, phosphates, oxides, and hydroxides of lithium, sodium, magnesium, potassium, and calcium;
[0016] The heteroatom source is at least one of organic or inorganic salts containing sulfur, phosphorus, selenium, and boron;
[0017] The dispersant includes at least one of water, ethanol and acetone.
[0018] In the preparation process of the one-dimensional nanoreactor of the preparation method of the present invention, a precursor composed of a metal source, a carbon-nitrogen source, a supplementary carbon source, and an alkaline metal salt is sintered, and a one-dimensional nanoreactor with excellent performance can be obtained at one time. Specifically, it includes: first, the effective dispersion of the materials by mixing in a dispersant and under a stirring / grinding environment, and secondly, with a suitable drying method, the ratio of raw materials in the precursor is ensured to remain unchanged while avoiding solid-liquid chromatography of the materials, which will effectively facilitate the one-dimensional tubular molding and the uniform distribution of catalyst particles in the tube. Therefore, the present invention improves the generation and property stability of the one-dimensional nanoreactor through the mutual coordination between the various steps in the preparation method, especially the regulation of the material ratio.
[0019] The alkaline metal salt added in the present invention is a dehydration catalyst and a molecular template. As a dehydration catalyst, at low temperatures, it catalyzes the dehydration reaction in the carbon precursor, inhibits the formation of tar, promotes carbonization and aromatization, thereby increasing the carbon yield, and will not be consumed in this process. At higher temperatures, it can be used as a molecular template to produce micropores. This is because the sufficiently dispersed molten alkaline metal salt will remain inside the carbon material, which can inhibit the carbonization of the carbon and nitrogen source, the shrinkage caused by shrinkage, and the deformation collapse. Finally, the material is impregnated with acid / water, and the porosity is released. The through-holes caused by the molten salt and the good thermal conductivity of the molten salt itself ensure the uniformity of heating and enhance the thermal efficiency. Therefore, this is one of the keys to ensure that the morphology of the material remains stable after the expansion of production. Through the above effects, the final pyrolysis mass loss is only 70%, and the final product output can reach more than 10% of the raw material mass, reducing the unusable ash, greatly improving the yield compared to the traditional pyrolysis method, and greatly reducing the production cost. The carbon-nitrogen source, supplementary carbon source and heteroatom source added in the present invention can affect the mass ratio of elements such as nitrogen, carbon, boron and sulfur contained in the carbon layer, which can further improve the material structure stability, electronic conductivity and other properties.
[0020] The inventors also found that the dispersion degree of metal in the raw material and the ratio of metal source to supplementary carbon source directly affect the morphology and size of the product. Therefore, by adjusting the appropriate ratio of metal source to supplementary carbon source, the metal is dispersed to an appropriate degree, which overcomes the problem of difficult control of metal particle size and uneven carbon tube morphology in the traditional pyrolysis method. In addition, the preparation method of the present invention has a simple preparation process and can directly utilize materials that have been industrialized, such as production lines and production equipment of lithium iron phosphate, silicon-carbon negative electrodes, etc., and the cost of conversion is low.
[0021] As a preferred embodiment, the mixing method includes at least one of ball milling, grinding and stirring; the drying includes at least one of normal pressure drying, spray drying, freeze drying and boiling drying.
[0022] As a preferred solution, the mixing, drying and sintering steps are performed at least once or in combination. Mixing, drying and sintering in combination or multiple times can produce one-dimensional nanoreactors with different morphologies and structures; for components with different raw material compositions and different proportions, the process can also be adjusted by mixing, drying and sintering in combination or multiple times.
[0023] As a preferred solution, the process further includes the following steps: drying the mixed liquid slurry to obtain a first precursor, crushing the first precursor and mixing it again to obtain a second precursor, and sintering the second precursor to obtain a one-dimensional nanoreactor. The process has simple equipment requirements, and the drying process only requires the simplest normal pressure drying, which is suitable for the case where the agglomerates are large after the first drying. By crushing and mixing it again, the morphology of the sintered one-dimensional nanoreactor can be made more uniform.
[0024] As a preferred solution, the process further includes the following steps: drying and sintering the mixed liquid slurry simultaneously to obtain a one-dimensional nanoreactor. This process combines the drying and sintering steps and is suitable for situations where the raw material composition is simple and the morphology of the generated one-dimensional nanoreactor is easy to control.
[0025] As a preferred solution, the following steps are also included: the metal source is mixed with the supplementary carbon source and dried, and then sintered once to obtain a one-dimensional nanoreactor preform; the one-dimensional nanoreactor preform is mixed with the carbon-nitrogen source, alkaline metal salt, and heteroatom source, and then dried, and then sintered twice to obtain a one-dimensional nanoreactor. This process is suitable for situations where the raw material composition is complex and the product is difficult to form in one go. Multiple sintering can better control the size of metal particles, maintain the uniform morphology of the one-dimensional nanoreactor, and reduce the pyrolysis mass loss.
[0026] As a preferred solution, a thickener is further added during the mixing, and the added amount of the thickener is 0.1-2 wt % of the dispersant. The thickener includes at least one of polytetrafluoroethylene, polyethylene glycol, and hydroxypropyl methylcellulose.
[0027] The role of thickener mainly includes four parts:
[0028] ① Improve slurry uniformity: Thickeners help to evenly distribute particles in the precursor slurry, prevent solid matter from settling or agglomerating in the slurry, and ensure that the proportions of the various components of the material before calcination are consistent, thereby ensuring the uniformity of the final calcined product.
[0029] ② Enhance shape retention ability: Before calcination, the precursor material needs to be shaped. The thickener can increase the viscosity of the slurry so that it can maintain the desired shape and structure before drying and calcination, avoiding material collapse or deformation at high temperatures.
[0030] ③ Control the release of moisture and volatile substances: The thickener can adjust the moisture content in the slurry, slowly release moisture or volatile substances during the calcination process, avoid cracking or holes caused by rapid evaporation of water, and ensure a dense material structure after calcination.
[0031] ④ Improve calcination efficiency: By controlling the rheological properties of the slurry, the thickener can optimize the thermal decomposition and reaction process of the precursor material, help the precursor to be more evenly converted into the target material during the calcination process, and improve the purity and performance of the final product.
[0032] As a preferred embodiment, the sintering is carried out in a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, argon, hydrogen, ammonia, and methane; the sintering conditions are: heating at a rate of 0.1 to 10 ° C / min, rising to 300 to 1400 ° C, and keeping warm for 2 to 24 hours. By adding a protective atmosphere, the loss of raw material quality can be greatly reduced, the loss of raw material quality can be reduced to less than 60%, and the final product output can reach more than 20% of the raw material quality. More preferably, the sintering has multiple stage temperatures, illustratively, 600 ° C for 2 hours, then 700 ° C for 4 hours, and finally 900 ° C for 2 hours. This process is determined according to the reaction between the reactants. The purpose of setting the temperature and time is to ensure the completeness of the reaction. The appropriate sintering temperature, sintering time and heating rate during sintering can improve the completion of the reaction, so as to obtain a one-dimensional nanoreactor material with stable properties. If the sintering process is not set reasonably, it may lead to uneven morphology of the product, a large loss of raw materials, etc.
[0033] Second aspect:
[0034] A one-dimensional nanoreactor prepared by the preparation method described in the first aspect is a carbon nanotube, a carbon nanoprism or a long-range carbon nanotube, which is a carbon layer wrapped around metal nanoparticles doped with heteroatoms with a particle size of 2-200nm; the metal nanoparticles include at least one of a metal element, an alloy, a phosphide, a sulfide, a nitride, a carbide, and an oxide; and the heteroatoms include at least one of sulfur, phosphorus, selenium, and boron.
[0035] Charge transfer can occur between metal nanoparticles and heteroatom-doped carbon layers. Furthermore, electrons on the surface of heteroatom-doped carbon layers are transferred to metal nanoparticles, which will help improve the ion transmission rate and conductivity of the carbon layer surface, and at the same time improve the catalytic conversion ability of metal nanoparticles. And its long-range ordered tubular structure can form a well-interconnected structure, ensuring the connectivity between materials. It can be applied to various application fields such as energy storage and catalysis.
[0036] The third aspect:
[0037] An application of the one-dimensional nanoreactor as described in the second aspect in a lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic diagram of the preparation process of a one-dimensional nanoreactor;
[0039] Figure 2 is a SEM image of the long tubular B, N co-doped Fe3C@CNT prepared in Example 1;
[0040] Figure 3 is a SEM image of the long tubular B, N co-doped Fe3C@CNT prepared in Example 1;
[0041] Figure 4 is a TEM image of the long tubular B, N co-doped Fe3C@CNT prepared in Example 1;
[0042] Figure 5 is the XRD pattern of the long tubular B, N co-doped Fe3C@CNT prepared in Example 1;
[0043] Figure 6 is a SEM image of the spherical / short tubular B, N co-doped Fe3C@CNT prepared in Example 2;
[0044] Figure 7 is a TEM image of the spherical / short tubular B, N co-doped Fe3C@CNT prepared in Example 2;
[0045] Figure 8 is a SEM image of the prismatic B, N co-doped Fe3C@CNT prepared in Example 3;
[0046] Fig. 9 is a TEM image of the prismatic B, N co-doped Fe3C@CNT prepared in Example 3;
[0047] Fig.10 is the XRD pattern of B and N co-doped Fe3C@CNT prepared in Examples 4, 5 and 6;
[0048] Fig.11 is the XRD pattern of B and N co-doped Mn5C2@CNT prepared in Example 7;
[0049] Fig.12 is the XRD pattern of B and N co-doped Co@CNT prepared in Example 8;
[0050] Fig.13 is the XRD diagram of pure Fe3C powder and Fe3C-CNT prepared in Comparative Example 1;
[0051] Fig.14 is a thermogravimetric analysis diagram of the positive electrode materials prepared in Example 1 and Comparative Example 3;
[0052] Fig.15 It is a lithium-sulfur battery cycle performance diagram of the positive electrode materials prepared in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0053] The method for preparing a one-dimensional nanoreactor according to the present invention comprises the following steps:
[0054] like Figure 1 As shown, a metal source, a carbon and nitrogen source, a supplementary carbon source, an alkaline metal salt, and a heteroatom source are placed in a dispersant, and a thickener is added to mix them to obtain a mixed liquid slurry;
[0055] Drying the mixed liquid slurry to obtain a precursor;
[0056] Sintering and cleaning the precursor to obtain a one-dimensional nanoreactor;
[0057] The molar ratio of the metal source, carbon and nitrogen source, supplementary carbon source, alkaline metal salt, and heteroatom source is (0.1-99): (5-30): (0-15): (0-10): (0-20);
[0058] The metal source includes at least one of nitrates, chlorides, sulfates, phosphates, oxides, and hydroxides of iron, manganese, nickel, cobalt, copper, zinc, or aluminum;
[0059] The carbon and nitrogen source includes at least one of urea, pyridine, polyaniline, cyanamide, dicyandiamide, melamine and dopamine.
[0060] The supplementary carbon source comprises at least one of citric acid, glucose, sucrose, starch, maltose, chitosan, polyvinyl pyrrolidone, polyethylene, polypropylene, polyethylene glycol, polyvinyl alcohol, and polystyrene;
[0061] The alkaline metal salt includes at least one of nitrates, chlorides, sulfates, sulfates, phosphates, oxides, and hydroxides of lithium, sodium, magnesium, potassium, and calcium;
[0062] The heteroatom source is at least one of organic or inorganic salts containing sulfur, phosphorus, selenium, and boron;
[0063] The dispersant includes at least one of water, ethanol and acetone;
[0064] The thickener comprises at least one of polytetrafluoroethylene, polyethylene glycol and hydroxypropyl methylcellulose, and the added amount of the thickener is 0.1-2 wt % of the dispersant.
[0065] The mixing, drying and sintering steps are performed at least once or in combination; the mixing method includes at least one of ball milling, grinding and stirring; the drying includes at least one of atmospheric pressure drying, spray drying, freeze drying and boiling drying;
[0066] The sintering conditions are: heating the temperature to 300-1400° C. at a heating rate of 0.1-10° C. / min and keeping the temperature for 2-24 hours.
[0067] The one-dimensional nanoreactor is a carbon nanotube, a carbon nanoprism or a long-range carbon nanotube, which is composed of a carbon layer wrapping metal nanoparticles doped with heteroatoms with a particle size of 2-200nm; the metal nanoparticles include at least one of a metal element, an alloy, a phosphide, a sulfide, a nitride, a carbide, and an oxide; and the heteroatoms include at least one of sulfur, phosphorus, selenium, and boron.
[0068] Lithium-sulfur battery positive electrode material testing:
[0069] Weigh sulfur powder and one-dimensional nanoreactor material in a mass ratio of 7:3, mix them thoroughly, heat them to 155° C. and melt the sulfur in a reactor for 12 hours to obtain a sulfur-loaded one-dimensional nanoreactor material positive electrode material;
[0070] The obtained sulfur-loaded one-dimensional nanoreactor material, carbon black conductive agent (Super P) and polyvinylidene fluoride (PVDF) binder were mixed in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) was added, ground into a paste in an agate mortar, applied on the current collector aluminum foil, and then placed in a 60°C vacuum drying oven for 8 hours, and cut to prepare the pole piece. Then they were all transferred to a glove box filled with argon gas for assembly of button cells. The button cell model was CR2032, with a metal lithium sheet as the counter electrode, a polypropylene microporous membrane Celgard 2400, and an electrolyte of 1 mol / L LiPF6 / EC+DMC+EMC (V / V / V=1:1:1). The assembled lithium-sulfur battery was tested for electrochemical performance on the Xinwei test system, with a voltage range of 1.7 to 2.8V.
[0071] Example 1
[0072] The preparation process of the long tubular N and B co-doped Fe3C@CNT one-dimensional nanoreactor of the present invention comprises the following steps:
[0073] Add ferric chloride hexahydrate, melamine, glucose, anhydrous calcium chloride and boron oxide in a molar ratio of 5:12:2:2.5:1 to ethanol, and add polytetrafluoroethylene, wherein the amount of polytetrafluoroethylene added is 1wt% of ethanol, and place in a vacuum mixer after mixing, stir for 4 hours to obtain a mixed liquid slurry; transfer the mixed liquid slurry to a drying oven and dry at 80°C for 12 hours to obtain a precursor. Place the precursor in a tubular rotary kiln, pass nitrogen, wash for 1 hour, then increase the temperature to 350°C at 5°C / min for two hours, then increase the temperature to 600°C at 5°C / min for 4 hours, and finally increase the temperature to 900°C at 2.5°C / min for 2 hours. After cooling, wash and obtain a long tubular N, B co-doped Fe3C@CNT one-dimensional nanoreactor powder.
[0074] Sulfur powder and long tubular N, B co-doped Fe3C@CNT one-dimensional nanoreactor powder were weighed in a mass ratio of 7:3, mixed thoroughly, and heated to 155°C to melt the sulfur in a reactor for 12 hours to obtain sulfur-loaded long tubular N, B co-doped Fe3C@CNT one-dimensional nanoreactor powder lithium-sulfur battery positive electrode material.
[0075] Figure 2 and Figure 3 The large-field and small-field SEM images of the long tubular N and B co-doped Fe3C@CNT one-dimensional nanoreactor are shown in Figure 2. Figure 2 It can be seen that this is a long-range tubular one-dimensional nanoreactor with a large aspect ratio. Under a wide field of view, it can be seen that it has a dense texture. Figure 3 It can be seen that the one-dimensional nanoreactor has uniform morphology and uniform diameter; Figure 4 This is the TEM image of a long tubular N, B co-doped Fe3C@CNT one-dimensional nanoreactor. It can be seen that the one-dimensional nanoreactor is encapsulated with metal nanoparticles; Figure 5 This is the XRD pattern of the long tubular N and B co-doped Fe3C@CNT one-dimensional nanoreactor, which shows that N and B atoms are successfully doped.
[0076] Example 2
[0077] The preparation process of a spherical tubular N and B co-doped Fe3C@CNT one-dimensional nanoreactor of the present invention comprises the following steps:
[0078] Add ferric chloride hexahydrate, melamine, glucose, anhydrous calcium chloride and boron oxide in a molar ratio of 5:12:3:2.5:1 to ethanol, and add polyethylene glycol, wherein the amount of polyethylene glycol added is 0.5wt% of ethanol, and place the mixture in a vacuum mixer, stir for 4 hours to obtain a mixed liquid slurry; transfer the mixed liquid slurry to a drying oven and dry it at 80°C for 12 hours to obtain a precursor. Place the precursor in a tubular rotary kiln, pass nitrogen, wash for 1 hour, then increase the temperature to 350°C at 5°C / min for two hours, then increase the temperature to 600°C at 5°C / min for 4 hours, and finally increase the temperature to 900°C at 2.5°C / min for 2 hours. After cooling, the spherical tubular N, B co-doped Fe3C@CNT one-dimensional nanoreactor powder is obtained after washing.
[0079] Figure 6 and Figure 7 The SEM and TEM images of the spherical tubular N and B co-doped Fe3C@CNT one-dimensional nanoreactor are shown in Figure 2. Figure 6 It can be seen that this is a long-range one-dimensional nanoreactor shaped like beads. Figure 7 This is the TEM image of the spherical tubular N and B co-doped Fe3C@CNT one-dimensional nanoreactor. It can be seen that the material is also wrapped with metal nanoparticles.
[0080] Example 3
[0081] The preparation process of the prism-shaped N and B co-doped Fe3C@CNT one-dimensional nanoreactor of the present invention comprises the following steps:
[0082] Ferric chloride hexahydrate, melamine, glucose, anhydrous calcium chloride, and boron oxide in a molar ratio of 5:12:1:2.5:1 are added to ethanol, and hydroxypropyl methylcellulose is added, wherein the amount of hydroxypropyl methylcellulose added is 2wt% of ethanol, and the mixture is placed in a vacuum mixer and stirred for 4 hours to obtain a mixed liquid slurry; the mixed liquid slurry is transferred to a drying oven and dried at 80°C for 12 hours to obtain a precursor. The precursor is placed in a tubular rotary kiln, nitrogen is introduced, and the gas is washed for 1 hour, then the temperature is kept at 350°C at 5°C / min for two hours, then the temperature is increased to 600°C at 5°C / min for 4 hours, and finally the temperature is increased to 900°C at 2.5°C / min for 2 hours. After cooling, the prism-shaped N, B co-doped Fe3C@CNT one-dimensional nanoreactor powder is obtained after washing.
[0083] Figure 8 and Fig. 9 The SEM and TEM images of the prismatic N and B co-doped Fe3C@CNT one-dimensional nanoreactor are shown in Figure 2. Figure 8 It can be seen that this is a one-dimensional nanoreactor composed of multiple long-range prisms. Fig. 9 This is the TEM image of the spherical tubular N, B co-doped Fe3C@CNT one-dimensional nanoreactor. It can be seen that larger metal nanoparticles are attached to the material.
[0084] It can be seen from Examples 1-3 that the morphology of the one-dimensional nanoreactor can be controlled by adjusting the ratio of the raw materials.
[0085] Example 4
[0086] The preparation process of a N and B co-doped Fe3C@CNT one-dimensional nanoreactor of the present invention comprises the following steps:
[0087] After ferric chloride hexahydrate and melamine in an ethanol solvent with a molar ratio of 5:12 are uniformly dissolved, the mixed liquid slurry is dried to obtain a first precursor, and then it is mixed with glucose, anhydrous calcium chloride, and boron oxide in a molar ratio of 1:2.5:1, and polyvinyl pyrrolidone is added, wherein the amount of polyvinyl pyrrolidone added is 0.5wt% of ethanol. Polyvinyl pyrrolidone can also be used to further disperse and fix the catalyst particles and provide a carbon source. After mixing, it is placed in a ball mill and dry-milled into powder to obtain a second precursor.
[0088] The precursor was placed in a tubular rotary furnace, nitrogen was introduced, and the gas was purged for 1 hour, then the temperature was raised to 350°C at 5°C / min and kept for 2 hours, then raised to 600°C at 5°C / min and kept for 4 hours, and finally raised to 900°C at 2.5°C / min and kept for 2 hours. After cooling, N and B co-doped Fe3C@CNT one-dimensional nanoreactor powder was obtained after washing.
[0089] Fig.10 There is an XRD pattern of the N, B co-doped Fe3C@CNT one-dimensional nanoreactor of Example 4, which shows that the N, B co-doped Fe3C@CNT was successfully synthesized.
[0090] Example 5
[0091] The preparation process of a N and B co-doped Fe3C@CNT one-dimensional nanoreactor of the present invention comprises the following steps:
[0092] Ferric chloride hexahydrate, melamine, glucose, anhydrous calcium chloride, and boron oxide in a molar ratio of 5:12:2:2.5:1 were added to ethanol, mixed and placed in a vacuum mixer, stirred for 4 hours to obtain a mixed liquid slurry; the mixed liquid slurry was directly placed in a tubular rotary kiln, nitrogen was introduced, and the gas was washed for 1 hour, then the temperature was increased to 350℃ at 5℃ / min for 2 hours, then increased to 600℃ at 5℃ / min for 4 hours, and finally increased to 900℃ at 2.5℃ / min for 2 hours. After cooling, long tubular N, B co-doped Fe3C@CNT one-dimensional nanoreactor powder was obtained after washing.
[0093] Fig.10 There is an XRD pattern of the N, B co-doped Fe3C@CNT one-dimensional nanoreactor of Example 5, which shows that the N, B co-doped Fe3C@CNT was successfully synthesized.
[0094] Example 6
[0095] The preparation process of a N and B co-doped Fe3C@CNT one-dimensional nanoreactor of the present invention comprises the following steps:
[0096] Ferric chloride hexahydrate, melamine, glucose, anhydrous calcium chloride and boron oxide in a molar ratio of 5:12:3:2.5:1 were added to ethanol, mixed and placed in a vacuum mixer, stirred for 4 hours to obtain a mixed liquid slurry; the mixed liquid slurry was transferred to a drying oven and dried at 80°C for 12 hours to obtain a precursor. The precursor was placed in a tubular rotary kiln, nitrogen was introduced, and the gas was washed for 1 hour, then the temperature was increased from 5°C / min to 350°C for 2 hours, and then taken out after cooling, which was a primary heating treatment precursor. The primary heating precursor was placed in a tubular rotary kiln, nitrogen was introduced, the gas was washed for 1 hour, the temperature was increased from 5°C / min to 600°C for 4 hours, and finally the temperature was increased from 2.5°C / min to 900°C for 2 hours. After cooling, the N and B co-doped Fe3C@CNT one-dimensional nanoreactor powder was obtained after washing.
[0097] Fig.10 There is an XRD pattern of the N, B co-doped Fe3C@CNT one-dimensional nanoreactor of implementation 6, which shows that the N, B co-doped Fe3C@CNT was successfully synthesized.
[0098] It can be seen from Examples 4-6 that the target product can be obtained by adjusting the process.
[0099] Example 7
[0100] The preparation process of the long tubular N and B co-doped Mn5C2@CNT one-dimensional nanoreactor of the present invention comprises the following steps:
[0101] Manganese chloride tetrahydrate, melamine, glucose, anhydrous calcium chloride and boron oxide in a molar ratio of 6:12:2:2.5:1 were added to ethanol, mixed and placed in a vacuum mixer, stirred for 4 hours to obtain a mixed liquid slurry; the mixed liquid slurry was transferred to a drying oven and dried at 80°C for 12 hours to obtain a precursor. The precursor was placed in a tubular rotary furnace, nitrogen was introduced, and the gas was washed for 1 hour, then heated to 350°C at 5°C / min for 4 hours, then heated to 600°C at 5°C / min for 4 hours, and finally heated to 900°C at 2.5°C / min for 6 hours. After cooling, N and B co-doped Mn5C2@CNT one-dimensional nanoreactor powder was obtained after washing.
[0102] Fig.11 There is an XRD pattern of the N, B co-doped Mn5C2@CNT one-dimensional nanoreactor of implementation 7, which shows that the N, B co-doped Mn5C2@CNT was successfully synthesized.
[0103] Example 8
[0104] The preparation process of the long tubular N, B co-doped Co@CNT one-dimensional nanoreactor of the present invention comprises the following steps:
[0105] Manganese chloride hexahydrate, melamine, glucose, anhydrous calcium chloride and boron oxide in a molar ratio of 4:12:2:2.5:1 were added to ethanol, mixed and placed in a vacuum mixer, stirred for 4 hours to obtain a mixed liquid slurry; the mixed liquid slurry was transferred to a drying oven and dried at 80°C for 12 hours to obtain a precursor. The precursor was placed in a tubular rotary furnace, nitrogen was introduced, and the gas was washed for 1 hour, then the temperature was increased to 300°C at 10°C / min for 4 hours, then increased to 600°C at 5°C / min for 4 hours, and finally increased to 900°C at 1°C / min for 2 hours. After cooling, the N and B co-doped Co@CNT one-dimensional nanoreactor powder was obtained after washing.
[0106] Fig.12 The XRD pattern of the N, B co-doped Co@CNT one-dimensional nanoreactor in Implementation 8 shows that the N, B co-doped Co@CNT was successfully synthesized.
[0107] A series of one-dimensional nanoreactor materials were prepared by changing the reaction raw materials and conditions using a method similar to Example 1, as shown in the following table:
[0108]
[0109]
[0110] Comparative Example 1
[0111] Ferric chloride hexahydrate, melamine, glucose and anhydrous calcium chloride in a molar ratio of 5:12:3:2.5 were added to ethanol, mixed and placed in a vacuum mixer, stirred for 4 hours to obtain a mixed liquid slurry; the mixed liquid slurry was transferred to a drying oven and dried at 80°C for 12 hours to obtain a precursor. The precursor was placed in a tubular rotary furnace, nitrogen was introduced, and the gas was washed for 1 hour, and then the temperature was kept at 700°C at 5°C / min for 1 hour. After cooling, pure Fe3C powder was obtained after washing.
[0112] After Fe3C powder and CNT in a mass fraction ratio of 2:8 were mixed in an ethanol solvent, the mixture was ultrasonically treated with an ultrasonic cleaner for 30 minutes, and then placed in an oven to evaporate the solvent to obtain a comparison sample Fe3C-CNT.
[0113] Sulfur powder and Fe3C-CNT material were weighed in a mass ratio of 7:3, mixed thoroughly, and heated to 155° C. to melt the sulfur in a reactor for 12 hours to obtain a sulfur-loaded Fe3C-CNT-S lithium-sulfur battery positive electrode material.
[0114] Fig.13 It is the XRD diagram of pure Fe3C powder and Fe3C-CNT prepared in comparative example 1.
[0115] Comparative Example 2
[0116] Sulfur powder and carbon nanotube (CNT) material were weighed in a mass ratio of 7:3, mixed thoroughly, and heated to 155° C. to melt the sulfur in a reactor for 12 hours to obtain a sulfur-loaded CNT-S lithium-sulfur battery positive electrode material.
[0117] Comparative Example 3
[0118] The conventional process was used to prepare a N and B co-doped Fe3C@CNT one-dimensional nanoreactor for comparison, including the following steps:
[0119] The precursor was obtained by grinding ferric chloride hexahydrate, melamine and boron oxide in a molar ratio of 5:12:1. The precursor was placed in a tubular rotary kiln, nitrogen was introduced, and the gas was washed for 1 hour, then the temperature was increased to 350℃ at 5℃ / min for 4 hours, then increased to 600℃ at 5℃ / min for 4 hours, and finally increased to 900℃ at 2.5℃ / min for 6 hours. After cooling, N and B co-doped Fe3C@CNT one-dimensional nanoreactor powder was obtained after washing.
[0120] Fig.14 This is a thermogravimetric analysis of Example 3 and Example 1. It can be seen that Example 1 has a higher raw material utilization rate through improvements in formulation and process.
[0121] Effect test
[0122] Take the sulfur-loaded positive electrode material obtained in Example 1 and Comparative Examples 1-2, carbon black conductive agent (Super P) and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, add an appropriate amount of N-methylpyrrolidone (NMP), grind to a paste in an agate mortar, apply it on the current collector aluminum foil, and then place it in a 60°C vacuum drying oven for 8h, and cut to prepare the pole piece. Then transfer them to a glove box filled with argon gas for assembly of button cells. The button cell model is CR2032, with a metal lithium sheet as the counter electrode, a polypropylene microporous membrane Celgard 2400, and an electrolyte of 1 mol / L LiPF6 / EC+DMC+EMC (V / V / V=1:1:1). The assembled lithium-sulfur battery was tested for electrochemical performance on the Xinwei test system, and the voltage range was 1.7 to 2.8V.
[0123] Fig.15 It is a lithium-sulfur battery cycle performance diagram of positive electrode materials prepared in Example 1, Comparative Example 1 and CNT. It can be seen from the figure that the positive electrode material prepared in Example 1 has a capacity retention rate of 70.2% after 500 cycles at a rate of 1C; the positive electrode material prepared in Comparative Example 1 has a capacity retention rate of only 57.5 after 500 cycles at a rate of 1C; and the capacity retention rate of the untreated CNT (Comparative Example 2) decays to 32.3% after 500 cycles at a rate of 1C.
[0124] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a one-dimensional nanoreactor, characterized in that: The following steps are involved: Mixing a metal source, a carbon and nitrogen source, a supplemental carbon source, an alkaline metal salt, and a heteroatom source in a dispersant to obtain a mixed liquid slurry; Drying the mixed liquid slurry to obtain a precursor; Sintering the precursor to obtain a one-dimensional nanoreactor; The molar ratio of the metal source, carbon and nitrogen source, supplementary carbon source, alkaline metal salt, and heteroatom source is (0.1-99): (5-30): (0-15): (0-10): (0-20); The metal source includes at least one of nitrates, chlorides, sulfates, phosphates, oxides, and hydroxides of iron, manganese, nickel, cobalt, copper, zinc, or aluminum; The carbon and nitrogen source includes at least one of urea, pyridine, polyaniline, cyanamide, dicyandiamide, melamine and dopamine. The supplementary carbon source comprises at least one of citric acid, glucose, sucrose, starch, maltose, chitosan, polyvinyl pyrrolidone, polyethylene, polypropylene, polyethylene glycol, polyvinyl alcohol, and polystyrene; The alkaline metal salt includes at least one of nitrates, chlorides, sulfates, sulfates, phosphates, oxides, and hydroxides of lithium, sodium, magnesium, potassium, and calcium; The heteroatom source is at least one of organic or inorganic salts containing sulfur, phosphorus, selenium, and boron; The dispersant includes at least one of water, ethanol and acetone.
2. The method for preparing a one-dimensional nanoreactor according to claim 1, characterized in that: The mixing method includes at least one of ball milling, grinding, and stirring; the drying includes at least one of normal pressure drying, spray drying, freeze drying, and boiling drying.
3. The method for preparing a one-dimensional nanoreactor according to claim 2, characterized in that: The mixing, drying and sintering steps are performed at least once or in combination.
4. The method for preparing a one-dimensional nanoreactor according to claim 3, characterized in that: The following steps are also included: The mixed liquid slurry is dried to obtain a first precursor, the first precursor is crushed and mixed again to obtain a second precursor, and the second precursor is sintered to obtain a one-dimensional nanoreactor.
5. The method for preparing a one-dimensional nanoreactor according to claim 3, characterized in that: The following steps are also included: The mixed liquid slurry is dried and sintered simultaneously to obtain a one-dimensional nanoreactor.
6. The method for preparing a one-dimensional nanoreactor according to claim 3, characterized in that: The following steps are also included: The metal source and the supplementary carbon source are mixed, dried, and then sintered once to obtain a one-dimensional nanoreactor preform; the one-dimensional nanoreactor preform is mixed, dried, and then sintered twice to obtain a one-dimensional nanoreactor.
7. The method for preparing a one-dimensional nanoreactor according to claim 1, characterized in that: A thickener is also added during the mixing, and the amount of the thickener added is 0.1-2wt% of the dispersant. The thickener includes at least one of polytetrafluoroethylene, polyethylene glycol, and hydroxypropyl methylcellulose.
8. The method for preparing a one-dimensional nanoreactor according to claim 1, characterized in that: The sintering is carried out in a protective atmosphere, which includes at least one of nitrogen, argon, hydrogen, ammonia and methane. The sintering conditions are: heating the temperature to 300-1400° C. at a heating rate of 0.1-10° C. / min and keeping the temperature for 2-24 hours.
9. A one-dimensional nanoreactor prepared by the method for preparing a one-dimensional nanoreactor according to any one of claims 1 to 8, characterized in that: The one-dimensional nanoreactor is a carbon nanotube, a carbon nanoprism or a long-range carbon nanotube, which is composed of a carbon layer wrapping metal nanoparticles doped with heteroatoms with a particle size of 2-200nm; the metal nanoparticles include at least one of a metal element, an alloy, a phosphide, a sulfide, a nitride, a carbide, and an oxide; and the heteroatoms include at least one of sulfur, phosphorus, selenium, and boron.
10. Use of the one-dimensional nanoreactor as claimed in claim 9 in a lithium-sulfur battery.
Citation Information
Patent Citations
Co-doped double-layer C-N compound nanomaterial as well as preparation method and application thereof
CN107394218A
Preparation method of cobalt-nickel-nitrogen co-doped carbon nanotube catalyst and application thereof
CN111229280A
Preparation method of lithium ion battery cathode material transition metal sulfide / carbon
CN115241443A
Carbon-based nanoreactor and preparation equipment and preparation process thereof
CN118162081A
Method for manufacturing electrocatalyst for fuel cell and use thereof
WO2012086597A1
Cited By
Modified fly ash for zinc-bromine flow battery positive electrode and preparation method and application thereof
CN122800633A